Review of the Genesis of Plant Pathology and Its Relation to the Phytiatry as a Necessary Element in the Sustainable Development of Agronomy - José Del Moral de la Vega; Jerónimo Del Moral Martínez (Agronomy, 2023)
The origin of plant pathology as a scientific discipline can be traced back to botany in the 18th century. In the following century, with the contributions of De Bary and Kühn, this discipline was able to identify the causes of diseases, learn about their development, and propose therapeutic measures, which is why these two researchers are considered to be the fathers of plant pathology. This account of its genesis is the one that appears in the histories currently published about it, but the discoveries of other authors who participated in its origin, whose work had not been taken into account, modify their knowledge. Among these authors are De Candolle and Blanco Fernández. The establishment of plant pathology, with a generalist, multidisciplinary, and integrative sense, as an academic discipline in the nineteenth century, disappeared together with some of the historical figures responsible for it, when other disciplines were born from it, and yet it is coincident with the current concept of phytiatry of the twenty-first century. The power to re-establish the characters and facts responsible for this historical moment allows us to review the current concept of phytiatry so that it fits with the greatest possible precision as a necessary tool for the sustainable development of agronomy as well as food security and is established as an indispensable part of a single global health concept.